Assessing the Effectiveness of Mindfulness-Based Stress Reduction (MBSR) Programs in Reducing Anxiety and Depression in Chronic Illness Patients - Kusumawati, Prima Dewi; Anshoriyah, Sofiyatul; Siokain, Delvy Mardvin; Fernandez, Fransisca Debby Christine; Nurhidayati, Wa Ode (International Journal of Public Health Excellence (IJPHE), 2025)
The objective of the present study was to evaluate the efficacy of a mindfulness-based stress reduction (MBSR) program in mitigating anxiety and depression levels in patients suffering from chronic illnesses. To this end, qualitative research techniques were employed, encompassing in-depth interviews and participant observation, in order to gather data from a cohort of twelve patients who had engaged in the MBSR program for a duration of 8 weeks at Sam Marie Clinic.Thematic analysis was subsequently implemented for the purpose of data analysis. Findings indicated that the MBSR program effectively reduced anxiety and depression levels by fostering heightened self-awareness, acceptance of emotions, and effective stress management.The study's findings offer crucial insights for the advancement of mindfulness-based psychosocial interventions in chronic disease patient care.